Promoting EFL students’ accuracy and fluency through interactive practice activities - McDonough, Kim; Sato, Masatoshi (Studies in Second Language Learning and Teaching, 2019)
This study examined the effectiveness of interactive activities at facilitating EFL students’ production of English relative clauses. Thirty-seven EFL learners in Chile carried out interactive activities designed to elicit relative clauses. Pre- and posttests were used to examine whether carrying out the activities facilitated the students’ production of relative clauses. All interactions were audio-recorded and the transcripts were analyzed to determine how accurately and fluently the students produced relative clauses before, during, and after the practice activities. Whereas accuracy was defined as errors involving relative clause formation, fluency was operationalized in terms of the number of pauses, false starts, and self-corrections that occurred within relative clauses. The results showed that the students produced significantly more accurate relative clauses on the posttest; however, their production of dysfluencies remained unchanged. Implications for the use of interactive activities are discussed.